2006
DOI: 10.1099/jmm.0.46734-0
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of Vibrio cholerae O1 strains similar to pre-seventh pandemic El Tor strains during an outbreak of gastrointestinal disease in an island resort in Fiji

Abstract: Five strains of Vibrio cholerae O1, one each from an Australian and a New Zealand tourist with gastrointestinal illness returning from an island resort in Fiji and the remaining three from water sources located in the same resort, were extensively characterized. Conventional phenotypic traits that are used for biotyping of O1 V. cholerae categorized all five strains as belonging to the El Tor biotype. Genetic screening of 11 regions that are associated with virulence in V. cholerae showed variable results. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
19
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 15 publications
(8 reference statements)
0
19
0
1
Order By: Relevance
“…In 2009, an outbreak occurred in PNG, eventually reaching 8,997 cases by the end of 2010, with the highest incidence in the Madang Province [95], [96]. In addition, an outbreak was reported from a resort in Fiji [97]. In Australia, four cases, all imported were reported in 2009.…”
Section: Bacterial and Fungal Ntdsmentioning
confidence: 99%
“…In 2009, an outbreak occurred in PNG, eventually reaching 8,997 cases by the end of 2010, with the highest incidence in the Madang Province [95], [96]. In addition, an outbreak was reported from a resort in Fiji [97]. In Australia, four cases, all imported were reported in 2009.…”
Section: Bacterial and Fungal Ntdsmentioning
confidence: 99%
“…These incidents included a large outbreak in west Pakistan in 1968 and the appearance of the classical biotype in Bangladesh in 1979, with a continuous presence until the end of 1992 (5). However, since 2001, a series of reports have been published revealing clinical isolates, from as far back as the early 1990s, that are of El Tor biotype background but possess some classical biotype traits (3,4,28,34,35,36,43). For example, the ctxA gene, which is the first gene of the ctx phage operon and codes for the A subunit of the cholera toxin, is completely conserved in sequence between the two O1 biotypes.…”
mentioning
confidence: 99%
“…These clinical El Tor O1 strains were found to contain the classical biotype cholera toxin B subunit gene (ctxB) and have since been termed El Tor variants (34,39). These El Tor variants have become a major focus of research, since other El Tor variants also have been identified in Asia and Mozambique (29,34,35,38) and recently have been a focus of attention in Haiti (1,6,7,8,9). Of particular concern are the recently published results indicating that some of the clinically isolated El Tor variants produce different levels of cholera toxin, including some isolates that produce higher levels than classical biotype strains (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This set of protocols details some of the different genetic and phenotypic assays commonly utilized when characterizing Vibrio cholerae clinical or environmental isolates (Lan and Reeves, 2002;Nair et al, 2002Nair et al, , 2006aAnsaruzzaman et al, 2004Ansaruzzaman et al, , 2007Safa et al, 2006). Basic Protocol 1 details a genetic screen commonly used to examine the sequences of the cholera toxin B subunit (ctxB; Nair et al, 2006a;Morita et al, 2008;Chatterjee et al, 2009) and the major pilin protein TcpA (tcpA; Safa et al, 2008;Chatterjee et al, 2009). Cholera toxin, composed of the A and B subunits, is the major virulence factor that is directly responsible for the rice-water diarrhea associated with The proteolysis assay performed on milk agar plates is suggestive of HapR-regulated protease activity.…”
Section: Introductionmentioning
confidence: 99%